Central nervous system intravascular lymphoma in a Malaysian. - Mohamed Mukari, Shahizon Azura; Ramli, Norlisah; Al-Edrus, Sharifah Aishah; Noordin, Mazin; Rahmat, Kartini; Looi, Lai Meng; Ganesan, Dharmendra; Gan, Gin Gin; Tan, Chong Tin (ASEAN Neurological Association, 2011)
Intravascular lymphoma (IVL) is a rare subtype of extranodal diffuse large cell lymphoma, characterized by intravascular proliferation of B or T lymphocytes within small blood vessels; which may lead to occlusive symptoms, its neurological involvement has been said to be uncommon among Asians. 1 We describe a Malaysian with central nervous system IVL, to demonstrate that IVL is an important differential diagnosis in diffuse brain pathology also among Asians.